Značilnosti prsti na pobočju Tičnice pri Rakeku - Lovrenčak, Franc (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1997)
Soil depths change in short distances on the karstic surface. This has been also confirmed by an investigation performed on Tičnica hill at Rakek in the Notranjsko valley system where the soil depths vary between 20 and 110 cm. This is due to the tectonically broken and corroded dolomite. On the locations where deeper fissures occurred in dolomite parent material, the soil is deeper. In such deeper profiles, reddish clay Brz horizons occur. From profile morphology, the position of horizon, and gentle slopes a conclusion has been derived, that clay particles are the insoluble residue of parent material weathering, that have remained in the place of origin.
Keywords: dolomit; fizična geografija; Inner Carniola; kamnine; Notranjska; pedogeografija; physical geography; Rakek; tla